Hubungan Asupan Zat Gizi dan Status Gizi Terhadap Kejadian Menstruasi Dini Pada Siswi SMPN 05 Kendari - Tina, Lymran (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2014)
Adolescence is a transition period in the human life span that connects childhood and adulthood. Early menstruation in adolescents is caused by their nutritional status and this cannot be separated from the role of nutrition consumed by adolescents. One of the effects of early menstruation is anemia in adolescents. This study aims to determine the relationship between nutrient intake and nutritional status on the incidence of early menstruation in female students of SMPN 05 Kendari. This research is a descriptive analytic research with a cross sectional study design. The population in this study were all students of SMPN 05 Kendari in 2014 as many as 94 people and a sample of 76 people who were taken using purposive sampling. The data was obtained using questionnaires and anthropometric measurements and tested using the Chi-Square test. The results obtained were from 40 adolescents whose energy consumption was sufficient, most of them, namely 22 people (55.0%) experienced early menstruation, from 29 adolescents who consumed sufficient protein, most of them, namely 17 people (58.6%) experienced early menstruation, Of the 27 adolescents who consumed less fat, most of them, namely 19 people (70.4%) experienced normal menstruation, of the 31 adolescents who consumed sufficient carbohydrates, the majority, namely 18 people (58.1%) experienced normal menstruation, from 32 adolescents who consumption of nutritional status is more, most of them, namely 20 people (62.5%) experienced early menstruation. It was concluded that there was a relationship between energy intake, protein, fat, carbohydrate and nutritional status with the incidence of early menstruation in junior high school students 05 Kendari. The suggestion in this study is that the results of this study can be input for local governments and related agencies in this case the Kendari City Health Office and SMPN 05 Kendari in determining policies in an effort to overcome nutritional status problems and early menstruation in adolescent girls. For the community, especially parents of teenagers, they should increase awareness of health status, especially about the importance of maintaining nutritional intake so that things can be avoided that can threaten the health status of the community, especially young women who have experienced menstruation. For health workers, it is necessary to provide counseling to young women so that they can increase and reduce their intake of energy, protein, fat and carbohydrates. For other researchers, should examine other factors associated with the incidence of menarche.